Child poverty in America today - Arrighi, Barbara A (Praeger, 2007)
In a 2004 study by the Annie E. Casey, Ford, and Rockefeller Foundations it was reported that a large number of American families are currently faring poorly in their struggle to provide for themselves. Low-income and poor families were found to contain one-third of all of the children in American working families. Low-wage jobs without benefits mean that families at or below the poverty line live a precarious existence. This four-volume set is designed to reveal, explicate, analyze, and assess the effects of an inadequate income on children. Each volume contains original essays written by an interdisciplinary roster of contributors.; Includes bibliographical references and indexes